2022
DOI: 10.22437/jmk.v11i2.17960
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Electronic Word of Mouth Terhadap Keputusan Pembelian Dengan Kepercayaan Konsumen Sebagai Mediasi Pada Marketplace Shopee Di Kota Jambi

Abstract: Tujuan penelitian ini adalah untuk mengetahui pengaruh Electronic word of mouth terhadap keputusan pembelian dengan kepercayaan konsumen sebagai mediasi pada marketplace shopee di Kota Jambi. Pengumpulan untuk mendapatkan data menggunakan survei dengan memberikan kuesioner yang kepada 100 responden yang berada di Kota Jambi. Untuk menguji data menggunakan alat analisis Smart PLS 3. Hasil yang didapatkan pada penelitian menunjukkan bahwa Electronic word of mouth berpengaruh langsung dan signifikan terhadap kepu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
1
3
0
1
Order By: Relevance
“…This shows that the higher the E-WOM received by consumers, the higher their purchase intention for the product or service offered. The results of this study agree with research conducted by (Nur & Octavia, 2022) which concluded that E-WOM has a positive and significant effect on purchase intention.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This shows that the higher the E-WOM received by consumers, the higher their purchase intention for the product or service offered. The results of this study agree with research conducted by (Nur & Octavia, 2022) which concluded that E-WOM has a positive and significant effect on purchase intention.…”
Section: Discussionsupporting
confidence: 91%
“…The more positive E-Wom is, the more it creates consumer confidence to decide to buy. The results of research by (Nur & Octavia, 2022) E-Wom is mediated by consumer confidence positively and significantly on purchasing decisions.…”
Section: Trust Mediates Electronic Word Of Mouth (E-wom) On Purchase ...mentioning
confidence: 88%
See 2 more Smart Citations
“…Word of Mouth tidak berpengaruh terhadap kesadaran merek, hal ini sejalan dengan penelitian yang dilakukan oleh: (Octavia, A., & Fatricia, 2017), (Nur & Octavia, 2022), (Wijaksono & Ali, 2019).…”
Section: Pembahasan Pengaruh Word Of Mouth Terhadap Kesadaran Merekunclassified